Water Productivity of Garlic (Allium sativum L.) under the Responsive Drip Irrigation (RDI) System Compared to the Drip and Furrow Irrigation Systems in Silty Loam Soil - Akbar, Ghani; Islam, Zafar; Ahmad, Bashir (The Nucleus, 2023)
Rapid population growth and climate change-induced water scarcity are challenging food security. Therefore, growing more food with less water and energy is urgently needed. The innovative responsive drip irrigation (RDI) system recently introduced in Pakistan responds to plant demand for water and nutrients and may be helpful in achieving this goal. Therefore, the yield, irrigation input and water productivity of garlic (Allium sativum L.) were evaluated under the RDI in comparison with the drip irrigation (DI) and furrow irrigation (FI) system (control) under silty loam soil at Islamabad, Pakistan. The treatments were three times replicated in a randomized block design. The average results show a significant (94%, 48%) water saving for the RDI and DI respectively than the FI (443 mm). The average dry garlic yield was also higher (3%, 11%) for the RDI and DI treatments respectively than the FI (13.491 tons/ha). Consequently, reducing irrigation water input and increasing crop yield resulted in a significant (94%, 46%) increase in the water productivity of garlic for the RDI and DI systems respectively than the FI (1.536 kg/m3). Thus, the newly introduced RDI system in Pakistan has indicated the prospects of increasing the yield and water productivity of garlic at the household level. Hence, promoting the concept and principles of the RDI system may be helpful in enhancing climate change resilience in water-scarce areas and vegetable production at household levels in urban areas, which may enhance local food and nutrition security in the country.